Ekonomi Masjid: Studi Baitul Maal Wa Tamwil (BMT) Kota Solok - Ilhamdi Yusra (UIN Imam Bonjol Padang, 2022)
This paper aims to discuss how the mosque's economy is through Baitul Maal wa Tamwil (BMT) Solok City. Solok City BMT is a non-governmental organization in the economic field and has become an icon of Solok City in order to realize the mission of Solok City, which is to become the